Hubungan Perhatian Orang Tua Dengan Karakter Kristiani Remaja (Usia 12-15) Di Desa Pegagan Julu V Kecamatan Sumbul Kabupaten Dairi Tahun 2023 - Contesa Sianturi; Pestaria Naibaho; Dame Taruli Simamora; Malani Simanungkalit; Meditatio Situmorang (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2023)
The aim of this research is to determine the relationship between parental attention and the Christian character of adolescents (aged 12-15) in Pegagan Julu V Village, Sumbul District, Dairi Regency in 2023. The method used in this research is a quantitative method with an inferential descriptive statistical approach. The population is all Christian teenagers (aged 12-15) in Pegagan Julu V Village, Sumbul District, Dairi Regency in 2023, totaling 103 people and a sample of 56 people was determined using random sampling techniques. Data was collected using a positive closed questionnaire with 47 items. 1) From the results of the calculation of the positive relationship test, the value of rxy = 0.616 > rtable(a=0.05,n=56) = 0.254 is obtained, thus it is known that there is a positive relationship between variable X and variable Y. 2) Test a significant relationship The value obtained is tcount= 5.745 > ttable(a=0.05,dk=n-2=54)=2.000, thus there is a significant relationship between variable X and variable Y. So Ha says there is a relationship between parental attention and adolescent Christian character. (ages 12-15) In Pegagan Julu V Village, Sumbul District, Dairi Regency, 2023 is accepted and H0 is rejected.